Pengaruh Agresivitas Pajak, Return On Asset, Dan Size Terhadap Pengungkapan Corporate Social Responsibility di Masa Pandemi Covid-19 (Studi Pada Perusahaan Sektor Industri Dasar dan Kimia di Bursa Efek Indonesia Periode 2017-2019) (UNIVERSITAS ISLAM MALANG, 2022)
Abstract The COVID-19 pandemic has resulted in the industrial sector being one of the affected, due to the large number of people working from home. This study aims to determine the effect of tax aggressiveness, return on assets and size on the corporate social responsibility of companies affected by COVID-19, especially the basic and chemical industries on the IDX for the 2017-2019 period. A quantitative approach was chosen in this study. This study obtained the results: (1) tax aggressiveness, return on assets and size affect CSR simultaneously. (2) Tax aggressiveness partially has no significant effect on corporate social responsibility. (3) Return on assets has no significant effect on corporate social responsibility. (4) Size has a significant effect on corporate social responsibility. Therefore, the higher the disclosure of tax aggressiveness, return on assets and size, the higher the corporate social responsibility given. Conversely, the lower the level of disclosure of tax aggressiveness, return on assets and size, the lower the corporate social responsibility provided by the company. Keywords : Tax Aggressiveness, Return On Assets, Size, Corporate Social Responsibility